MASS BALANCE SIMULATION AND ITS APPLICATION TO REFINING FLOW FIELD IN BINCHANG AREA, CHINA - Li Yu.; Wang J.; Wu Ya.; Xu Zh.; Fu X.; Hou G. (My University, 2007)
Groundwater flow fields in aquifers are often determined by water level data measured in monitoring wells. The flow field can be further refined by mass balance simulations, especially when groundwater level data is limited. The mass balance simulation is based on the principle of mass conservation and relies on water quality data in the same aquifer. The approach is applied to the Luohe aquifer in the Binchang area, China. The water-rock interactions and the hydrogeochemical evolution were studied along four typical flow paths. The study indicates that groundwater in the Luohe formation flows from the southern border to the interior of the Ordos Basin. The southern border, approximately 1,400 km2, is a recharge zone, where the Luohe formation outcrops. The total dissolved solids of the groundwater in the southern boarder are less than 1 g/l, and the hydrochemistry type is HCO3–Na. This new finding refines the flow field of the water-bearing formation, and an additional 1,400 km2 is included in the water resource planning of the area.
Keywords: MASS BALANCE SIMULATION; GROUNDWATER FLOW FIELD; HYDROCHEMISTRY; LUOHE FORMATION; CHINA